Penerapan Metode Vikor untuk Menentukan Pemberian Dana Mekaar Plus pada PNM Kota Binjai - Enno Loria (MES Bogor, 2022)
PT Permodalan Nasional Madani or PNM, is here as a solution to improve welfare through access to capital, assistance and capacity building programs for business actors. Along with business development, in 2016, PNM launched a capital loan service for underprivileged women who are ultra micro business actors through the Fostering a Prosperous Family Economy (PNM Mekaar) program. For this reason, PNM must be more careful and considerate in determining the provision of Mekaar Plus loans. In order not to make mistakes and cause disappointment in the future. So it is necessary to build a system that can be used as a determining and alternative system in determining how to provide Mekaar Plus funds by using a decision support system. This system will be able to make decisions quickly and precisely according to predetermined criteria. So that in the process of giving the blooming funds it can be done more effectively and can reduce the occurrence of errors in the decision-making process. There are many methods used in the decision-making process. One of the methods used in this research is the Vise Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) method. Keywords: Decision Support System, PNM, Mekaar, VIKOR